PERIODONTITIS AND CARDIOVASCULAR DISEASE AS A SHARED CLINICAL CHALLENGE IN PATIENT CARE - KHAN, MI; HAMZA, M; ATHAR, M; ALI, AA; HASHMI, M; HAQ, UU; SAJID, M (Biological and Clinical Sciences Research Journal, 2023)
Cardiovascular disease (CVD) remains the leading cause of death, accounting for approximately one-third of all deaths worldwide. The primary aim of the study is to find the link between periodontitis and cardiovascular disease as a shared clinical challenge in patient care. This retrospective observational cohort study was conducted in Jinnah Medical and Dental College Karachi from May 2023 to August 2023. The study included a total of 230 patients from a diverse patient population. Patient data were collected meticulously through a comprehensive dental and medical records review. A total of 230 patients were included in this retrospective observational cohort study. Patient demographics, including age and gender, were documented to provide an overview of the study population. The study included 230 patients with a mean age of 45. 55% of the participants were male, and 45% were female. Based on clinical measurements, 35% of patients showed mild periodontitis, 45% moderate periodontitis, and 20% severe periodontitis. Radiographic evidence of bone loss was observed in 60% of the patients. 40% of the patients had a documented history of cardiovascular diseases, including coronary artery disease, myocardial infarction, stroke, or hypertension.It is concluded that a significant association between periodontitis and cardiovascular diseases has been found. While the precise mechanisms remain fully understood, these findings underscore the importance of comprehensive healthcare that considers both oral and cardiovascular health.